Análisis del periodismo sensacionalista en las noticias de farándula desde la visión de los estudiantes de la Carrera de Comunicación, Programa Online Agárrate - Coello Pincay, Elvira Magoly (2021)
The purpose of the investigation is to know the point of view of the students of the Communication career, about sensational journalism, which is carried out in the digital program Hold on. In addition to knowing and distinguishing the correct use of the content offered in the Grab program, along with the social responsibility that contributes to having a better critical society of its principles and values. It is aimed mainly at the students and the community in general of the Technical University of Babahoyo, and all people who contribute ideas to research, especially advanced semester students. The research had as support, texts and scientific documents related to the subject to argue the theoretical foundations, applied methodologies and the respective implemented research techniques, the sample applied a type of student probabilistic, allowing to throw results through surveys with appropriate justification and necessary for the development of a plan to report entertainment news, from an academic, ethical and social responsibility point of view